Delegation or Voting - Otto H. Swank; Bauke Visser (Tinbergen Institute, 2002)
Collective decision procedures should balance the incentives they provide toacquire information and their capacity to aggregate private information. In a decisionproblem in which a project can be accepted or rejected once information about its qualityhas been acquired or not, we compare the performance of a delegation structure with that oftwo voting procedures. Delegation makes one's acceptance decision pivotal by definition.The decisiveness of one's vote in a voting procedure depends on the other agent's vote.This in turn determines the decision to acquire information. In the debate about a rationalchoice foundation of Condorcet's Jury Theorem, the distribution of information was leftexogenous. Mixed (acceptance) strategies were required to validate the Theorem.Endogenizing information acquisition as we do reveals mixed (acceptance) strategies to bedetrimental for welfare as they lead to indifference between buying and not buyinginformation.
Keywords: D72; 330; Voting; Jury theorem; Information; Effort; Abstimmungsregel; Neue politische Ökonomie; Theorie